Upaya Peningkatan Kecerdasan Emosional Dalam Pembelajaran Akidah Akhlak Melalui Strategi Pembelajaran Ekspositori Berbasis Online Pada Siswa Kelas VIII MTS An Nadia Lubuk Jaya - Ahmad Fuadi; Rhadiatul Husna (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The problem in this research is that the teacher does not build students' critical awareness in learning. The teacher explains more about student knowledge or knowledge transfer without knowing whether the knowledge given is understood well or not. The purpose of this study is to find out how to increase students' emotional intelligence in learning Akidah Akhlak through the application of expository learning strategies to class VIII students of MTs Swasta An-Nadia Lubuk Jaya. This type of research is Classroom Action Research (PTK). According to the type of research chosen, namely classroom action research, this research, the analysis technique uses an action research model in the form of a spiral and from one cycle to the next. The results or conclusions from this study are that the average percentage of students through the results of the observation sheet includes the student character sheet in the first cycle, which is 64.76%, and the second cycle, which is 81.38%. This shows that the students have followed the learning process well which is marked by an increase in student intelligence at each meeting. Then student learning outcomes after using expository learning strategies have increased. In the analysis of test results in cycles I and II it can be seen that there is an increase in student learning outcomes, namely in cycle one students who have a complete score of 12 students or 70.6% and in the second cycle students completed 15 students or 88.24%